Early Detection of Diabetic Foot Peripheral Neuropathy With The Michigan Neuropathy Screening Instrument (Mnsi): A Scoping Review - Oper, Nunung Khairun Nissa; Kristianto, Heri; Yuliatun, Laily (Jurnal Health Sains, 2023)
Background: Neuropathy is a major cause of morbidity and mortality in type 1 and 2 diabetes worldwide. The development of neuropathy and its severity increases with increasing duration of DM and poor glycemic control. Early detection of neuropathy is essential to prevent worse disease complications. Objective: to identify a simple instrument MNSI in detecting peripheral neuropathy of diabetic foot. Methods: Scoping review protocol using 5 steps of Aksey and O'Malley Framework. Inclusion criteria were published in 2016-2023, full text, English language and discussed the use of MNSI in detecting peripheral neuropathy. This article used 4 databases (Pubmed, ProQuest, and ScienceDirect) with the keywords "Michigan screening instrument AND diabetic neuropathy AND early detection". Results: There were 10 articles that fit the inclusion criteria that mentioned that MNSI is a simple tool in detecting peripheral neuropathy in diabetic foot. Conclusion: MNSI is a reliable instrument, easy to do and can be used by doctors, nurses, and health workers involved in the treatment of patients with diabetes mellitus